A Maternity Hospital in Shenyang Indoor Environment Performance Influence Factor Analysis. (2016) - Yu, Liang; Chen, Shuang; Jia, Ji; Ding, Ran; Wang, Siwen
Abstract: In recent years, the city air pollution level of PM2.5, ozone, nitrogen oxides and sulfur dioxides in our country occupies first place. Indoor environmental problems caused by outdoor air pollution are increasingly significant. Indoor environment of hospital which is a special public building has special requirement. The feature of maternity hospital is crowded, heavy energy consumption, weakness of maternal and neonate, generate the sick and the patients need the better indoor environment quality. Therefore, this paper takes hospital building as research object by using questionnaire method, which analyzes the indoor comprehensive environmental performance of hospital, such as the air quality, the thermal environment, the light environment, and the acoustic environment. Results show that most of the patients is satisfied with the indoor comprehensive environmental performance of hospital, and only a small part is dissatisfied with the sound environment and the outdoor vision. This paper provides a research base for establishing a complete evaluation system and method of comprehensive indoor environmental performance of maternity hospital, which will help in building environmental monitoring systems and improving the level of public participation in the construction of hospital management.